Analysis of cost of various topical and oral antifungal drugs for superficial fungal infections available in India - V., Spoorthy H.; Padma, L.; P., Srividya B. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: In tropical countries like India, superficial fungal infections are quite common and certain infections like tinea is rampantly spreading in epidemic proportions and frequent relapses after treatment have increased the need for long term therapy significantly increasing the cost of treatment, so the treatment of fungal infection can raise economic burden on the patient. The aim of the study was to analyze the cost variation of topical antifungal drugs and oral antifungal drugs of various brands for superficial fungal infection available in India. Methods: Cost in Indian Rupees (INR) of antifungal agents manufactured by different pharmaceutical companies in India was collected from the Current index of medical specialities (CIMS) October to December 2019. Minimum cost, maximum cost, cost ratio, cost variation was calculated. Results: In oral dosage form, fluconazole, Itraconazole show the maximum cost variation. In topical single drug therapy luliconazole, terbinafine show maximum cost variation. Conclusions: There is wide cost variation among antifungal agents available in Indian Market. There is need of strict actions for cost policy regulation and sensitization of doctor for selection of appropriate brand drugs.